Personal Hygiene Behavior in Karema District of Mamuju West Sulawesi - Iqbal Ahmad; Suriah; Indra Fajarwati Ibn; Firnasrudin Rahim (Politeknik Karya Persada Muna, 2022)
Baground: Clean and Healthy Living Behavior (PHBS) is a form of realization of healthy living orientation in individual, family, and community cultures, which aims to improve, maintain, and protect their health both physically, mentally, spiritually, and socially. This study aims to determine the attitude of the family, subjective norms, and perceivedbehavioral control personal hygiene.Method: This type of research is a qualitative research case study approach. The selection of informants by snow balling the number of informants 18 people. Data collection such as interview guides and observation sheets, validity through triangulation of data sources and triangulation methods. Processing and data analysis using interactive analysis and presented in narrative form.Result: The results showed that the attitude of informants on personal hygiene behaviors that informants respond withpersonal hygiene agree to behave and think is clean and protected from disease when doing so. There are also informants who perform personal hygiene behavior based on personal encouragement and there is also the informant who behaves personal hygiene because of information from health professionals, however, they are carried out depends on the facilities available.Conclusion: This is recommended that post health workers should do more frequent counseling so that the community in Karema Village understands about better personal hygiene and the community understands more about diseases caused by lack of personal hygiene efforts.Keyword : Behaviour, personal hygiene